Association Between Health Behaviours during Menstruation and Endometriosis - Sanaz Mollazadeh (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Endometriosis is characterised by implantation of endometrium outside the uterine cavity. There are numerous risk factors for this disease. Aim: To study the association between health behaviours during menstruation and endometriosis as one of the various risk factors for this disease. Materials and Methods: This case-control study recruited 555 women visiting a hospital in North West of Iran. The case group comprised 185 women of reproductive age with confirmed diagnosis of endometriosis through laparoscopy or laparotomy. The control group comprised 370 women without endometriosis visiting the hospital for other health problems. Data were collected using a researcher-made questionnaire; included socio-demographic and health behaviours characteristics based on previous studies. Univariate analysis was performed using the chi-squared test, and multivariate analysis was done using conditional logistic regression. Results: Based on multivariate logistic regression, the health behaviours of the two groups during menstruation were significantly different. Taking hot baths {OR (95% CI)=4.78 (2.22 to 10.30); p>0.001} and performing vaginal washing {OR (95% CI)=7.20 (1.32 to 39.22); p=0.022}, during menstruation increased the risk of endometriosis approximately five and seven times in those women who stated they took hot baths and performed vaginal washing during menstruation compared to those who stated they did not. Moreover, the chance of developing endometriosis was about two times higher in women who used cloth menstrual pad during menstruation than those who did not {OR (95% CI)=1.97 (1.12 to 3.44); p=0.017}. There was a significant difference between the two groups in terms of the average number of days in which they used cloth menstrual pad and the average number of cloth menstrual pad used per day. Conclusion: Based on the results, there is a relationship between taking hot baths and performing vaginal washing during menstruation as well as using cloth menstrual pad during menstruation and endometriosis.